Analysis of Food Security Status Among Farming Households in Kurfi Local Government Area of Katsina State, Nigeria - Adeola, Segun Solomon; Okome Bright (FUDMA Journal of Sciences, 2026)
The study analyzed food security status among rural farming households in Kurfi Local Government Area, of Katsina State. Using a two-stage sampling procedure, 100 farming households were selected for the study. Relevant data were collected from the selected households with the aid of structured questionnaire and analyzed using descriptive statistics, household food security index and binary logistics regression model. The findings show that most of the household heads are in their active age with an average age of 37.7 years, with most of them (75%) being males and majority (72%) of them are married with an average household size of 9 persons. The main occupation among the respondents is farming (44%) with an average years of farming experience of 11.70 years and most (81%) of them having formal education ranging between primary and tertiary education. The mean annual income of the household heads was ₦446,439.46. The Results equally showed that 58% of the households were food secure and 42% were food insecure. Results further revealed that the variables that significantly influenced household food security status in the study area include age (p<0.01) and household size (p<0.001). Buying less quality food to feed the family ranked top (68%) among the coping strategies used to ameliorate food insecurity. The study concluded that many households are still food insecure in the study area and recommends that government should subsidize agricultural inputs to encourage more food production in the area.